Interobserver and Intraobserver Reproducibility and Reliability of the Huashan Clinical Classification System for Hirayama Disease - Sun, Chi; Xu, Guangyu; Zhang, Yuxuan; Cui, Zhongyi; Liu, Dayong; Yang, Yong; Wang, Xiandi; Ma, Xiaosheng; Lu, Feizhou; Jiang, Jianyuan; Wang, Hongli (Frontiers in Neurology, 2021)
Purpose: The Huashan clinical classification system for Hirayama disease has recently been proposed and has been found useful for diagnosis and treatment. So far, however, there has been little in-depth evaluation of its reliability. Thus, this study aimed to assess the reproducibility and reliability of the system. Methods: Patients diagnosed with Hirayama disease between 2019 and 2020 were recruited. Seven spine surgeons from four different institutions, including an experienced group of three and an inexperienced group of four, were trained as observers of the Huashan clinical classification system for Hirayama disease, and these surgeons classified the recruited patients using the system. Then, 2 months later, they repeated the classification on the same patients in a different order. The interobserver and intraobserver agreement between the results was analyzed using percentage agreement and weighted kappa (κ) statistics. Results: A total of 60 patients were included in the analysis. For all the observers, experienced observers, and inexperienced observers, the agreement percentages were, respectively, 78.5% (κ = 0.76), 80.0% (κ = 0.78), and 78.9% (κ = 0.77), indicating substantial interobserver reproducibility. For distinguishing typical (Types I and II) and atypical (Type III) Hirayama disease among the different groups of observers, the percentage agreement ranged from 95.6 to 98.9% (κ = 0.74–0.92), indicating substantial to nearly perfect reproducibility. For suggesting conservative treatment (Types I and III) or surgery (Type II), the percentage agreement ranged from 93.3 to 96.4% (κ = 0.81–0.90), indicating nearly perfect reproducibility. As for intraobserver agreement, the percentage agreement ranged from 68.3 to 81.7% (κ = 0.65–0.79), indicating substantial reliability. Conclusion: The Huashan clinical classification system for Hirayama disease was easy to learn and apply in a clinical environment, showing excellent reproducibility and reliability. Therefore, it would be promising to apply and promote this system for the precise and individualized future treatment of Hirayama disease.